2017
DOI: 10.1111/bjep.12168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of achievement goals on perceptions of competence in conditions of unfavourable social comparisons: The mastery goal advantage effect

Abstract: Current findings broaden understanding of the adaptive nature of mastery-approach goals and suggest that it is possible to modulate aversive responses to unfavourable social comparisons by focusing attention on mastery-approach goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Students who pursue mastery goals are more likely to use adaptive learning strategies (e.g., Madjar et al, 2017), devote sustained efforts in school (Muenks et al, 2018), and experience well-being (see review Kaplan & Maehr, 2007). Recent findings suggested that endorsing academic mastery goals can also predict other important variables linked to students functioning such as attitudes toward social comparisons (Kamarova et al, 2017), life satisfaction (Diseth & Samdal, 2014), general well-being (Mastrotheodoros et al, 2017), and self-worth (Ben-Eliyahu et al, 2017). A longitudinal study that followed students’ interest and achievement in mathematics from elementary through middle school, revealed positive reciprocal relationships with their mastery and performance-approach goals and a negative reciprocal relationship with their performance-avoidance goals (Scherrer et al, 2020).…”
Section: Achievement Goal Orientationsmentioning
confidence: 99%
“…Students who pursue mastery goals are more likely to use adaptive learning strategies (e.g., Madjar et al, 2017), devote sustained efforts in school (Muenks et al, 2018), and experience well-being (see review Kaplan & Maehr, 2007). Recent findings suggested that endorsing academic mastery goals can also predict other important variables linked to students functioning such as attitudes toward social comparisons (Kamarova et al, 2017), life satisfaction (Diseth & Samdal, 2014), general well-being (Mastrotheodoros et al, 2017), and self-worth (Ben-Eliyahu et al, 2017). A longitudinal study that followed students’ interest and achievement in mathematics from elementary through middle school, revealed positive reciprocal relationships with their mastery and performance-approach goals and a negative reciprocal relationship with their performance-avoidance goals (Scherrer et al, 2020).…”
Section: Achievement Goal Orientationsmentioning
confidence: 99%
“…For Canadian students in 2005, a relationship was also reported between academic achievement and happiness (2). Higher academic achievement was also observed in teenagers with more happiness feeling (3,4). Currently, there is no integrated study to gather all data from published articles through a meta-analysis approach.…”
Section: Contextmentioning
confidence: 99%
“…This may be because mastery-approach goals are primarily linked to a pattern of adaptive educational outcomes ( Sommet and Elliot, 2017 ). An alternative reason is that students who possess mastery-approach goals have fewer negative psychological responses to wrong social comparisons ( Kamarova et al, 2017 ). This study confirmed that mastery-approach goals are a remarkably powerful goal type ( Shih, 2012 ) that considerably boosts academic adjustment.…”
Section: Discussionmentioning
confidence: 99%